463 BONE MARROW TREATED WITH WNT3A AND WNT5A RESULTS IN A CHANGE IN THE CELLULAR DISTRIBUTION OF DIFFERENTIATED AND UNDIFFERENTIATED INFLAMMATORY CELL TYPES. (10th December 2015) - Fathke, C.; Wilson, L.; Hocking, A.; Isik, F. F.
Abstract : Background: During adult cutaneous wound healing the acute inflammatory stage is essential for proper wound repair. Various conditions dysregulate the inflammatory phase and a chronic inflammatory cycle ensues. Chronic inflammation is characterized by the persistent presence of monocytes, lymphocytes and plasma cells in the injured region. It prevents epithelialization and results in the necrosis of the surrounding tissue. Chronic inflammation is thought to be the etiology for most non-healing wounds. It also remains one of the most elusive problems to characterize at the cellular and molecular level. It is not clear why the inflammatory process becomes dysregulated or exactly what molecular signals have gone awry. One of the candidates for the molecular signals involved in inflammation is the Wnt family of signaling molecules. These glycoproteins regulate proliferation and differentiation of cells by signaling through the Wnt/β-catenin or Wnt/Ca2+ pathways Recent work in our lab suggests that Wnt signal transduction may play a role in wound healing and in the regulation of inflammation during the cutaneous healing process. Our hypothesis is that the Wnt pathway is an adjuvant for inflammatory cell differentiation. Study Design and Methods: An in vitro model was used where whole bone marrow was extracted from the femur and tibia of TOPGAL mice and cultured for 24, 48 or 72 hours in conditioned media containing either control, Wnt3a, a mediator of the Wnt/